2021
DOI: 10.1002/acr.24240
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision‐Making Applied to Knee Arthroplasty: A Systematic Review of Randomized Trials

Abstract: Objective Shared decision‐making (SDM) is a strongly endorsed approach by which patients and clinicians work together to formulate a sensible care plan. The present study was undertaken to conduct a systematic review of SDM trials in patients considering knee arthroplasty (KA) to characterize how SDM was supported and the impact on care received. Methods We searched multiple bibliographic databases from inception to December 31, 2019. A pair of reviewers working independently selected studies for inclusion, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Positive effects of DAs related to decisional conflict and knowledge are reflected in previous studies[ 7 , 8 ]. Achaval et al [ 7 ] investigated the effect of an education booklet, video booklet and decision tool on the decisional conflict among patients with knee OA.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Positive effects of DAs related to decisional conflict and knowledge are reflected in previous studies[ 7 , 8 ]. Achaval et al [ 7 ] investigated the effect of an education booklet, video booklet and decision tool on the decisional conflict among patients with knee OA.…”
Section: Introductionsupporting
confidence: 57%
“…It showed a significant overall reduction in decisional conflict. A recent systematic review by Riddle et al [ 8 ] looked primarily at the effect of DAs on patients’ knowledge considering total knee arthroplasty. They found a positive effect on the knowledge of patients, but no effect on patients’ anxiety, satisfaction or decisional conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Shared decision making (SDM) has been widely advocated as a way to better set these expectations [ 9 ], by informing patients about the benefits and harms of TKA and non-surgical conservative management options which are effective [ 10 ], but underutilized [ 11 ]. Previous studies have found that using a patient decision aid to promote SDM can improve knowledge and the quality of decisions [ 12 ], overcoming common biases where individuals often overestimated an intervention's benefit and underestimated its harms [ 13 ]. However, these studies have typically not been conducted in routine care and so the results are potentially less generalizable [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no systematic review has been conducted on PtDAs for adults with OA considering primary elective THA and TKA decision-making. This review will complement the systematic review of Riddle et al [53] by focusing on PtDAs by (1) providing a summary of RCTs findings on PtDAs effect on decision-making quality and process of adults with knee and hip OA considering primary elective TJA and by (2) providing evidence comparing different types of PtDA used for hip and knee TJA decisionmaking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review exploring features and impact of SDM/PtDA interventions for knee arthritis TJA decision-making found that most trials did not include all key aspects of SDM [53]. The authors recognized the need for future research to focus on assessing the effect of PtDAs and SDM on treatment decision, functional outcomes, and satisfaction [53].…”
Section: Introductionmentioning
confidence: 99%